Model Eco-Nutri: Pendampingan Manajemen Lahan Sempit Untuk Ketahanan Pangan Keluarga dan Pencegahan Stunting - Merry Moy Mita; Nila Sari (Jurnal Pemberdayaan Masyarakat, 2025)
Stunting remains a significant national challenge in Indonesia, with a prevalence rate of 21.5% in 2023, where high food costs and the mismanagement of household assets such as underutilized small yards contribute to the vulnerability of toddler nutrition in rural areas like Adin Tengah Village. This community service program aimed to integrate economic management principles with public health interventions to foster household food self-sufficiency and mitigate stunting risks through the implementation of the "Eco-Nutri" model. The program was conducted over six months using a systematic four-stage approach consisting of social mapping, integrated education on financial literacy and nutrition, field implementation of vertical farming systems, and sustainability monitoring. Results indicated that the Eco-Nutri model successfully transformed 85% of previously idle land into productive gardens and led to a 25-30% reduction in daily household vegetable expenditures, allowing families to reallocate their budget toward high-quality animal proteins. Furthermore, nutritional literacy among participants increased by 65%, demonstrating that the integration of economic resource management and ecological nutrition is a strategic and effective approach to enhancing household resilience. In conclusion, the program established a sustainable model for long-term stunting prevention by empowering the community to optimize limited resources for better health and economic outcomes